2005
DOI: 10.1128/jb.187.5.1695-1701.2005
|View full text |Cite
|
Sign up to set email alerts
|

A Chimeric N-Terminal Escherichia coli -C-Terminal Rhodobacter sphaeroides FliG Rotor Protein Supports Bidirectional E. coli Flagellar Rotation and Chemotaxis

Abstract: Flagellate bacteria such as Escherichia coli and Salmonella enterica serovar Typhimurium typically express 5 to 12 flagellar filaments over their cell surface that rotate in clockwise (CW) and counterclockwise directions. These bacteria modulate their swimming direction towards favorable environments by biasing the direction of flagellar rotation in response to various stimuli. In contrast, Rhodobacter sphaeroides expresses a single subpolar flagellum that rotates only CW and responds tactically by a series of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 35 publications
1
6
0
Order By: Relevance
“…To elucidate the mechanisms that underlie the observed enhancement in motility and chemotaxis, we first examined how experimental evolution affected E. coli motility ( Figure S2 A). The most apparent phenotypic change in all evolved strains was increased swimming velocity in liquid: whereas velocity of the parental strain was comparable with that observed previously ( Morehouse et al., 2005 , Oleksiuk et al., 2011 ), it nearly doubled in some of the evolved strains. Moreover, the majority of evolved strains also exhibited an increased frequency of reorientations (tumbling rate).…”
Section: Resultssupporting
confidence: 86%
“…To elucidate the mechanisms that underlie the observed enhancement in motility and chemotaxis, we first examined how experimental evolution affected E. coli motility ( Figure S2 A). The most apparent phenotypic change in all evolved strains was increased swimming velocity in liquid: whereas velocity of the parental strain was comparable with that observed previously ( Morehouse et al., 2005 , Oleksiuk et al., 2011 ), it nearly doubled in some of the evolved strains. Moreover, the majority of evolved strains also exhibited an increased frequency of reorientations (tumbling rate).…”
Section: Resultssupporting
confidence: 86%
“…17and is given by (1/3)C 2 , with positive τ corresponding to the front of the cell, towards θ = 0, rotating clockwise and the aft rotating anticlockwise when viewed from behind, as depicted in Fig. 12, which corresponds to the chirality of E. Coli, whilst the opposite chirality is exhibited by R. Sphaeroides [49,50]. We therefore introduce another slip-velocity parameter, γ 2 , defined as γ 2 = C 2 /B 1 , to incorporate the rotary contribution of the tangential deformation.…”
Section: Swimmer With a Rotlet Dipolementioning
confidence: 99%
“…Besides, threonine has also been shown to promote swimming motility in bacteria. Morehouse et al (2005) has shown that threonine is present in the rotor protein FliG, which is important for rotation of flagella in term of directionality. This might explain how threonine enhanced the swimming motility in E. coli BL21 in this study.…”
Section: Journal Of Biology and Life Sciencementioning
confidence: 99%